Thrombophilic genetic anomalies and their association with dialysis initiation age in a cohort of Lebanese hemodialysis patients - Barbari, A. (2018)
OBJECTIVES:The relationship between chronic kidney disease and cardiovascular disease is complex and bidirectional. This relationship may be partially linked to thrombophilic genetic anomalies that may predispose to the progression of both diseases. MATERIALS AND METHODS:We analyzed blood samples from 102 Lebanese patients with end-stage renal disease and undergoing hemodialysis and 20 randomly selected healthy volunteers for frequencies of 12 cardiovascular disease gene mutations and traditional risk factors. The frequencies of these mutations were calculated and compared in both groups. We stratified patients by quartiles according to their mean score of genetic mutations and traditional risk factors, as well as their mean age at dialysis initiation. Correlation analyses were performed on the various patient groups. RESULTS:We observed a high frequency of mutations in patients on dialysis. Homozygous mutations (> 10% of patients) were observed in the PAI-1 (11%), MTHFR A1298C sequence variant (12.7%), and ACE genes (12%); in addition, the FXIII V34L and PAI-1 4G/5G genotypes were significantly associated with early dialysis initiation (P < .001 and P = .004, respectively). We observed a strong linear relationship between the different scores and age at dialysis initiation, with older patients exhibiting the highest genetic, traditional, and total scores versus those shown in the youngest patients (R2 = 0.72 and P < .001; R2 = 0.98 and P < .001; and R2 =0.96 and P < .001, respectively). CONCLUSIONS:Our results revealed a polygenic thrombophilic profile in our population of Lebanese patients with end-stage renal disease. This profile showed a strong association between early dialysis initiation and specific homozygous cardiovascular disease gene mutations. The cumulative load of these genetic and traditional risk factors may be partly responsible for the increased risk of cardiovascular disease and risk of progression to end-stage renal disease in patients with chronic kidney disease.